Association Between Depressive Symptoms and Mortality in Medical Inpatients - Furlanetto, Leticia M.; Von Ammon Cavanaugh, Stephanie; Bueno, Joao Romildo; Creech, Steven D.; Powell, Lynda H. (Psychosomatics (Washington, D.C.), 2000)
The authors interviewed a consecutive series of medical inpatients ( N = 241) using the Schedule for Affective Disorders and Schizophrenia to determine which depressive symptoms are associated with in-hospital mortality. Fifteen depressive symptoms, pain, and physical discomfort were assessed along with medical comorbidity. Twenty patients died in-hospital (8.3%). Logistic regression showed that anhedonia, hopelessness, worthlessness, indecisiveness, and insomnia predicted in-hospital death after adjusting for physical comorbidity and age. Clinicians should be aware that these depressive symptoms may predict mortality in medical inpatients. Future studies should address which treatment modalities lead to better outcomes.